PENERAPAN PENILAIAN AUTENTIK BERDASARKAN KURIKULUM 2013 PADA KOMPETENSI KEAHLIAN TEKNIK GAMBAR BANGUNAN DI SMK NEGERI WILAYAH DKI JAKARTA - Dinar Rosmawati; Tuti Iriani; Daryati Daryati (LPPM Universitas Negeri Jakarta, 2016)
This study aims to get information and the problem which is face by teacher about applied of authentic assessment base on curriculum 2013 in The Drawing of Buildings Engineering Program Expertise at 1 Vocational High School of Jakarta, 26 Vocational High School of Jakarta, and 35 Vocational High School of Jakarta.This study used survey method with data collection using structures interview techniques to get the information and the problem which is face by teacher about applied of authentic assessment base on curriculum 2013.The results of this study shown that the applied of authentic assessment base on curriculum 2013 in The Drawing of Buildings Engineering Program Expertise at Vocational High School Area of DKI Jakarta not going well. Because, just 29% respondents who have understanding the true of authentic assessment. RPP preparation only performed by 71% respondents and 100% respondents not preparation instruments realm of attitudes and skill but only preparation instrument of knowledge. However, almost all the teacher 95% respondents not conduction an analysis of the quality assessment instrument realm of knowledge that has been made. The follow up program given by 86% respondents for the students in the form of remedial activities. For the results of this study shown too that 86% respondents states find the problem in the applied of authentic assessment